Implementation of the Salam Agreement on the Sharia Marketplace Al Huda Market from a Sharia Economic Law Perspective - Adinda Satria Bagus; Syamsul Hidayat; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
This journal delves into the implementation of Salam transactions in accordance with Fatwa DSN MUI No 05/DSN-MUI/IV/2000, focusing on a profound understanding of the definition of Salam transactions, clear identification of goods and prices, and the aspects of transparency and clarity in agreements. Upfront payment is deemed crucial to avoiding speculative elements and ensuring contract fulfillment according to the principles of Salam transactions. Moreover, transactions must align with the principles of Islamic Sharia, including the avoidance of usury and uncertainty (gharar), necessitating thorough documentation. The journal recommends consultation with Sharia legal experts or scholars to ensure authenticity in compliance with the latest developments in fatwas or scholars' interpretations. Additionally, the paper reviews the implementation of Salam contracts on the Sharia-compliant marketplace, Pasar Al Huda, within the framework of Sharia Economic Law. Various parties, such as buyers, sellers, the delivered goods, and the contracting process (sighat), play vital roles in ensuring the smoothness and authenticity of transactions in the marketplace. Buyers bear the responsibility of understanding the legal aspects and transaction conditions, while sellers must comprehend the law, avoid breaching commitments, and ensure timely delivery as agreed upon. Key elements in executing Salam contracts include clarity in goods, prices, delivery times, and the expression of mutual consent (ijab qabul).